PENGELOLAAN PEMBELAJARAN BERBASIS MULTIPLE INTELLIGENCES (Studi Situs di SDIT Assalamah Ungaran Kab. Semarang) - MAHZUM , AHMAD (2011)
The purposes of this study are 1) To know the characteristics of grouping class on learning multiple intelligences approach in SDIT Assalamah Ungaran, 2). To know the characteristics of teachers and students interaction based on multiple intelligences approach in SDIT Assalamah Ungaran, 3). To know the characteristics of learning assessment of multiple intelligences in SDIT Assalamah Ungaran. Type and design of this study was descriptive qualitative research with ethnographic design. The study Site is SDIT Assalamah Ungaran Semarang District. Sources of data used in this study are the principal, teachers, staff and parents of students as well as documents. The data collection techniques in this study are interviews, observation and documentation study. The data analysis techniques in this study are domain analysis, taxonomi analysis, componential analysis and thema analysis. The results of this study Management of Multiple Intelligences Based Learning in SDIT Assalamah Ungaran are 1). Characteristics of grouping class on learning multiple intelligences approach in SDIT Assalamah Ungaran has followed the theory of Multiple Intelligences which was sparked by Dr. Howard Gardner, and in its development have been drawn by the experts into the world of education such as Thomas Armstrong and Bobbi DePorter, namely the presence of Multiple Intelligences Research (MIR) to each learner. 2). Characteristics of teachers and students interaction based on multiple intelligences approach in SDIT Assalamah Ungaran accordance with the principles of quality management based on "Total Quality Management" is by the application of Quality Control Management in learning tailored to the Multiple Intelligences learning approach into four cycles of learning management, lesson plans, consulting/sharing, observation and feedback. 3). Characteristics of learning assessment of of multiple intelligences in SDIT Assalamah Ungaran so fars using pattern-based assessment processes that include the domain: cognitive, affective and psychomotor, that used the assessment process both formative and summative uses of reference the following criteria: a). learning competency is developing competence learning matrix that ensures a targeted learning experience. b). Countinuous authentic assessment that is ongoing to develop an authentic assessment that ensures the achievement of competence and mastery.